Nutrition and oral health in early childhood: associations with formal and informal childcare. Issue 6 (28th April 2021) - Carpenter, Lauren; Gibbs, Lisa; Magarey, Anthea; Dashper, Stuart; Gussy, Mark; Calache, Hanny
Abstract: Objective: To examine associations between childcare type and nutrition and oral health indicators. Design: Cross-sectional data extracted from a longitudinal birth cohort. Parent-completed FFQ and questions regarding oral health and childcare use. The associations between childcare type, classified into four groups: parent care only (PCO), formal childcare only (FCO), informal childcare only (ICO) or combination of care (F&I), and nutrition and oral health indicators were examined. Setting: Home and childcare. Participants: Families with children aged 3 years ( n 273) and 4 years ( n 249) in Victoria, Australia. Results: No associations were observed between childcare type and core food/beverage consumption or oral health indicators. For discretionary beverages, compared with children receiving PCO at age 3 years, children in FCO or F&I were less likely to frequently consume fruit juice/drinks (FCO: adjusted OR (AOR) 0·41, 95 % CI 0·17, 0·96, P = 0·04; F&I: AOR 0·32, 95 % CI 0·14, 0·74, P = 0·008). At age 4 years, children receiving FCO or ICO were less likely to consume sweet beverages frequently compared with children receiving PCO: fruit juice/drink (ICO: AOR 0·42, 95 % CI 0·19, 0·94, P = 0·03; FCO: AOR 0·35, 95 % CI 0·14, 0·88, P = 0·03) and soft drink (ICO: AOR 0·23, 95 % CI 0·07, 0·74, P = 0·01; FCO: AOR 0·14, 95 % CI 0·03, 0·76, P = 0·02). Conclusions: Associations between childcare type and discretionary beverage intake were observed. Investigation into knowledge, attitudes and activities in formal and informal childcare settings is required to explore different health promotion practices that may influence nutrition and oral health.